Catalogação de histórias em quadrinhos à luz da semiótica da cultura - Pavarina, Etefania Cristina (Palabra Clave.)
This research discusses the documentary analysis of comics in a semiotics framework in order to guarantee library retrieval by users. Comic cataloging presents difficulties due to their being a resource that integrates both verbal and non-verbal language. The objective of this exploratory, qualitative and applied research is to look into the relationships that can be established between cataloging and semiotics of culture, in order to contribute to the theoretical and epistemological grounds of the organization and representation of information in comics. Through bibliographic procedures, the results are traced by means of the content analysis method. The concepts developed by the semiotics of culture can contribute to cataloging, mainly in the processes of document reading, subject analysis, and subject cataloging. The results demonstrate that the concepts of cultural semiotics allow defining aspects of the semiosphere of the author and the cataloguer, since both permeate the construction of the bibliographic record of comics. In conclusion, the cataloger, as a mediator, is in charge of understanding the cultural codes that make up the semiosphere of comics, thus assuring the user the conditions to satisfy their informational needs, through translation and transcoding.